2015
DOI: 10.2147/ndt.s83989
|View full text |Cite
|
Sign up to set email alerts
|

Rare and very rare adverse effects of clozapine

Abstract: Clozapine (CLZ) is the drug of choice for the treatment of resistant schizophrenia; however, its suitable use is limited by the complex adverse effects’ profile. The best-described adverse effects in the literature are represented by agranulocytosis, myocarditis, sedation, weight gain, hypotension, and drooling; nevertheless, there are other known adverse effects that psychiatrists should readily recognize and manage. This review covers the “rare” and “very rare” known adverse effects of CLZ, which have been a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
78
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 87 publications
0
78
0
1
Order By: Relevance
“…This monitoring for agranulocytosis (an absolute neutrophil count below 500/mm 3 ) was initiated after a study in 1975. In this study, 17 of 2,660 (0.7%) patients were diagnosed with agranulocytosis, and 8 of these patients died from infection after diagnosis 26. It has been shown that agranulocytosis may occur at any dose; therefore, patients taking even the smaller doses used in PDP must be closely monitored.…”
Section: Introductionmentioning
confidence: 80%
“…This monitoring for agranulocytosis (an absolute neutrophil count below 500/mm 3 ) was initiated after a study in 1975. In this study, 17 of 2,660 (0.7%) patients were diagnosed with agranulocytosis, and 8 of these patients died from infection after diagnosis 26. It has been shown that agranulocytosis may occur at any dose; therefore, patients taking even the smaller doses used in PDP must be closely monitored.…”
Section: Introductionmentioning
confidence: 80%
“…Although it is the gold standard in the treatment of resistant schizophrenia with a clear and established superior effectiveness than other APs [66], clozapine has a wide range of AEs, many of which are severe or life-threatening, even if most of the latter are relatively rare [67].…”
Section: Pharmacology and Mechanism Of Actionmentioning
confidence: 99%
“…The anticholinergic properties of clozapine as well as its H 1 antagonism were related to several grades of impairment of intestinal peristalsis ranging from transient-to-obstinate constipation and paralytic ileus up to intestinal obstruction [67]. Constipation is a very frequent reported AE (15%-60%) [98].…”
Section: Adverse Effectsmentioning
confidence: 99%
“…In the nonclozapine arm, it was assumed that ADRs did not occur and medications had no costs, so the costs reflected inpatient stays. Mortality was estimated by the effect of clozapine on suicide among veterans and anticipated mortality from serious ADRs (61)(62)(63). The business case for clozapine was broadened by multiplying the results over the treatment-eligible population within the VHA.…”
Section: Discussionmentioning
confidence: 99%
“…Pooled risks and mortality of the clozapine-related ADRs were calculated from studies identified through the literature review and the clozapine-prescribing information (7,(62)(63)(64). A pooled risk of clozapine-related seizures and subsequent risk of discontinuation were calculated from an analysis of the clozapine patient management system database (64).…”
Section: Clozapine-related Adrsmentioning
confidence: 99%